Does Vulnerable Youth Moderate the Relationship of Education, Training, and E-Learning on Sustainable Employment Generation and Social Empowerment? - Thu Hema Varni; Ikramina Larasati Hazrati Havidz (Mutiara: Multidiciplinary Scientifict Journal, 2024)
Purpose, he purpose of this study is to look at the effect of education, training and e-learning as well as emotional intelligence on sustainable employment generation and social empowerment with vulnerable youth as a moderator. Design/methodology/approach, The subjects of this study are workers with a maximum of 4 years experience and have used e-learning in Indonesia. The pre-test was conducted on 30 respondents and then collected 154 respondent data. Reliability and validity testing was carried out then the data was processed using SEM analysis. Findings, The results of this study show that SUEG and SEMP are positively and significantly influenced by ETL. EI affects SUEG positively and significantly. next VY moderated the relationship between ETL and SEMP negatively and not significantly. Then, VY moderated the relationship between ETL and SUEG negatively and significantly. Practical implications, It is hoped that the results of this research can become the basis for policies to improve the abilities and expertise of new graduates so that they are then able to reduce unemployment, poverty and displaced people. With the hope of strengthening economic growth and improving the welfare of the Indonesian people. Originality/value, Comprehensive research from the field of education and its impact on employment and social empowerment with the added influence of Emotional Intelligence and moderation from Vulnerable Youth is very rarely done so this becomes a scientific gap that must be filled.